Presenting Analytical Performances of Electrochemical Sensors. Some Suggestions. Issue 7 (10th June 2013) - Desimoni, Elio; Brunetti, Barbara
Abstract A description of the performances of new electrochemical sensors is important for evaluating their novelty and potential applicability to the analysis of real samples. However, it was noticed that quite often some figures of merit were ill‐defined or reported in an inadequate format. Based on some well‐known books and guidelines, some simple approaches are briefly reviewed which allow a better estimation of the most frequently reported figures of merit. Adopting these approaches implies a certain increase of cost and time of the given investigations. But the results would benefit from an easier acceptance by the scientific community.